Brottsoffer eller gärningsperson? Kriminalisering av deltagande i kriminella sammanslutningar och betydelsen för unga lagöverträdare i åldern 15–17 år - Andréewitch,Nora (2025)
In 2025, the government presented the report SOU 2025:2, Some Issues Concerning Fundamental Rights and Freedoms, which tasked a committee with, among other matters, examining whether the freedom of association should be restricted in relation to criminal organizations. The committee concluded that such measures should be introduced and a few months later Directive 2025:28, Criminalization of Participation in Criminal Organiza-tions, was presented assigning a special investigator the task of examining and proposing criminal liability for participation in a criminal organization. In 2023, the Swedish National Council for Crime Prevention (Brå) pub-lished a report addressing how children are recruited into (and treated after being recruited into) criminal networks. The report shows that children who are recruited often find themselves in vulnerable situations and that recruit-ment in many cases takes place through threats and violence. In several as-pects, the methods resemble sexual grooming. Brå’s report generated interest in examining the legal issues that may arise for the children involved in crim-inal organizations and has inspired the research question of this thesis: Is the criminalization of participation in criminal organizations legally acceptable considering how such legislation risks affecting the children who are active in the criminal activity in question? To examine the legal issues that may arise from such criminalization, several analytical tools are applied. The study adopts a clear child rights perspective, which, inter alia, entails that legislation and its application must be con-sistent with the UN Convention on the Rights of the Child. The thesis there-fore analyzes how a criminalization of participation in criminal organizations relates to several central provisions of the Convention. Furthermore, addi-tional analytical tools are applied, such as the requirement that a legal system should be coherent, the theory of the ideal victim, and the principle of cul-pability in criminal law. In addition, the question of whether children re-cruited into criminal networks can, in legal terms, be regarded as victims of crime is addressed. In order to answer the research question, a critical approach is applied along-side the legal dogmatic method. The study may be described as an “academ-ic referral response,” similar to what the Ombudsman for Children (BO) could submit in its capacity as a consultative body. The study shows that there are several reasons why a criminalization of par-ticipation in criminal organizations is not legally acceptable from a child rights perspective. Children who are recruited into criminal activity can in many cases be regarded as victims of crime, which means that they are af-forded protection under both national and international law. Such criminali-zation risks conflicting with several key provisions of the Convention on the Rights of the Child. The analysis further shows that these children do not correspond to the image of the ideal victim, while at the same time, their criminal liability may be questioned on the basis of the principle of culpabil-ity.
Keywords: straffrätt; barnkonventionen; brottsoffer; kriminell sammanslutning